User preferences of perspective and dimensionality of tourism space geovisualisation supporting orientation in a non-immersive virtual reality - Zajadacz, Alina; Halik, Łukasz (Quaestiones Geographicae, 2024)
The research problem was related to the search for appropriate parameters relevant to the tools that support spatial orientation in large-scale building plans. This problem was addressed by selecting the optimal (1) observation perspective (passerby perspective, bird-eye view perspective, top–down view perspective) in a non-immersive virtual reality (VR) and (2) the presentation dimensionality (2D/3D). The perception of the plans was analysed taking into account such independent variables as gender and the individual level of spatial orientation of the study participants, determined based on the Santa Barbara Sense of Direction (SBSOD) and the Mental Rotation tests (MRT). In the research conducted in 2021 on a sample of 103 people, the experimental methodology involved the comparison of preferences of the study participants in terms of geovisualisation before and after getting to know the real tourism space. The results showed the compliance of preferences, i.e. recognition as the optimal plan in 2D dimensionality and the top–down view perspective. No statistically significant differences in spatial orientation due to gender or individual predispositions measured by the SBSOD and the MRT tests were confirmed.